Impact of the use of artificial intelligence for digital content creation in multimedia engineering undergraduate students (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2024)
The study analyzed the impact of using artificial intelligence in digital content production among undergraduate students in Multimedia Engineering at Universidad Simón Bolívar, Cúcuta campus, during the academic semester 2023-2. It aimed to assess how this technology influences students' creative and technical skills development, as well as their creative autonomy, considering their understanding of authorship attribution and ethics in human-AI collaboration. Conducted within a positivist paradigm using deductive-logical quantitative design, data was collected through a survey of a simple random sample of 123 students from the total enrolled (178), with approximately 6% sample mortality. Findings revealed a dual perception regarding AI's impact on skill enhancement, showing both acceptance and skepticism. This highlights the diverse experiences encountered when Multimedia Engineering students decide to implement AI in their professional endeavors, emphasizing the pedagogical need to address AI in future professionals' education.
Keywords: Artificial intelligence; engineering; multimedia engineering; creativity and ethics